Practicing Biomedicine at the Albert Schweitzer Hospital 1913-1965 - Zumthurm, Tizian (Brill, 2020)
Tizian Zumthurm uses the extraordinary hospital of an extraordinary man to produce novel insights into the ordinary practice of biomedicine in colonial Central Africa. His investigation of therapeutic routines in surgery, maternity care, psychiatry, and the treatment of dysentery and leprosy reveals the inco-herent nature of biomedicine – and not just in Africa. Reading rich archival sources against and along the grain, the author combines concepts that appeal to those interested in the history of medicine and colonialism. Through the micro-cosm of the hospital, Zumthurm brings to light the social worlds of Gabonese patients as well as European staff. By refusing to easily categorize colonial medi-cal encounters, the book challenges our understanding of biomedicine as solely domineering or interactive. Readership: People interested in the history of medicine, especially in the colonies. Practitioners of Global Health. Students of Medical History. Historians of Africa. People interested in the work of Albert Schweitzer.